Clinical Presentation, Outcome and Risk Factors of Late-Onset Non- Infectious Pulmonary Complications After Allogeneic Stem Cell Transplantation - Patriarca, Francesca; Poletti, Venerino; Costabel, Ulrich; Battista, Marta L.; Sperotto, Alessandra; Medeot, Marta; Toffoletti, Eleonora; Fanin, Renato (Current Stem Cell Research & Therapy, 2009)
The term late-onset non-infectious pulmonary complications (LONIPCs) has been used to refer to events occurring later than 3 months after allogeneic hematopoietic stem transplant (HSCT), such as bronchiolitis obliterans, bronchiolitis obliterans with organizing pneumonia, and lymphocytic or idiopathic interstitial pneumonia. The incidence of LONIPCs varies widely, ranging between 10% and 26%. Median time for LONIPC development is about 8-12 months after HSCT. Clinical symptoms may be insidious and non specific at the beginning and can be present in different types of infections. The diagnosis is made on the basis of thoracic high-resolution computed tomography and pulmonary function tests (PFT). It usually requires that standard cultures for infective agents on bronchoalveolar lavage are negative and is confirmed by transbronchial or lung biopsy, whenever possible. Total body irradiation and high doses of drugs used in the conditioning regimens , HLA disparity between donor and recipient, and chronic graft-versus-host disease (GVHD) are the main risk factors for LONIPCs. Since patients with LONIPCs have an increased risk of mortality because of infections or respiratory failure, pre- and post-transplant PFTs are strongly recommended in order to timely identify affected patients. The administration of antithymocyte globulin before unrelated donor transplants and slow taper of cyclosporine after transplant have been shown to prevent chronic GVHD and, therefore, the occurrence of LONIPCs.
Keywords: pulmonary complications